Stress Estimation of Offshore Structures - Tarpø, Marius (AU Library Scholarly Publishing Services, 2020)
Offshore structures are subjected to a harsh environment where the fluctuating waves continuously strain the structures and these forces cause the initiation and propagation of cracks in the structures. In other words, the structures accumulate fatigue damage, which eventually leads to structural failure. To avoid fatigue failure, the operational lifetime of a structure is limited to a design lifetime in which the structure is safe for operation. This design process is based on precautious stochastic assessments, norms, and industry standards that simplify the actual structure and environment in such a manner that it involves little risk of structural failure. As many structures in the North Sea approach the end of their design lifetime, the owners are faced with a dilemma: either abandon the field or replace the structures. Another option is the lifetime extension of the existing structures. This requires a reduction of the uncertainties in the design process - such as the stress history in fatigue-critical location. Unfortunately, these locations are often inaccessible or directly harmful to the sensors due to the hostile environment of the ocean. This thesis focuses on virtual sensing to estimate the stress/strain response of offshore structures by indirect measurements. The thesis addresses the state of the art and maps some essential issues within stress/strain estimation. In this thesis, stress/strain estimation is applied to different test specimens to address certain scientific issues. Parts of the thesis relate to the calibration of the system model for virtual sensing by operational modal analysis.